Kajian Kriminologi Terhadap Pelaku Peredaran Rokok Non Cukai Di Luar Kawasan Perdagangan Bebas Tanjungpinang (International Forum of Researchers and Lecturers, 2024)
That the purpose of this research is to find out about the concept of criminology in the circulation of non-tax cigarettes in Non-Free Trade Areas (outside the Area) as well as to know how the role of the government in minimizing the problem. That this article uses the method of juridic research normative and makes an approach to the law. The sources of data used for this research to be valid are laws, books, journal articles, as well as web pages with similar topics in this article about non-tax cigarettes. The results of this study can be concluded that the criminology of non-tax cigarette trafficking perpetrators is divided into three main parts: criminal biology, which is the reason for the perpetrator, criminal sociology that is the background of circularity that can be the driving force of the non-tariff cigarette traffic and criminal policy that is an action that gives the effect that no other perpetrates follow the traffic and the role of the government in minimizing the circulation of cigarettes is by carrying out both direct and indirect surveillance. In addition, the government can also socialize to the public about tax obligations.